The Language and Portrayal of Compassion in National Health Service Hospital Advertising - Frenay, Clare (2014)
Abstract This paper explores the portrayal of compassion in NHS hospital advertising in the United Kingdom. Compassion is commonly defined as being sensitive to the suffering of others and showing a commitment to relieve it. Unacceptable reports of malpractice and patient neglect in recent press coverage have undermined the image of care staff being compassionate. Little has been researched about how this empathic mentality is increasingly demonstrated in on-site advertising displays and in the context of contemporary Government policy and guidelines for healthcare practice. The study entails a content and semiotic analysis of signage and poster publications in the built environments of two comparable large NHS hospitals in the Midlands during Autumn 2013. The content analysis samples feature 190 publications in each hospital which are further divided into groups. The semiotic analysis was conducted on theoretical samples of the original data set (9 publications in the established hospital and 20 in the new-build). Four main themes emerged from the data: (a) the opportunistic use of advertising to convey ï¿½compassionateï¿½ environments in the service provisions; (b) the portrayal of advanced nursing practitioners to emphasise the professional status of nursing; (c) the portrayal of idealistic care practices either to positively endorse caring or unduly raise expectation of quality and performance; (d) the significant presence of compassion-themed publications in the new Foundation Trust hospital. The study demonstrates the potential for hospital advertising to account for, promote and transform desirable visions of care in a rapidly changing health system.